Strategi Pengembangan Lada Putih dalam Mewujudkan Kawasan Sentra Produksi Nasional di Kabupaten Bangka Selatan - Pidia Lestari; Evahelda Evahelda; Yudi Sapta Pranoto (Journal of Integrated Agribusiness, 2019)
White pepper is one of the leading commodities in south Bangka Regency with production of 17.009 tons. It is used as a flavour enhancer in traditional culinary. This commodity also has the potential to improve the local economy. Its existence needs to be sustained considering the immense potential that it has among the problems surrounding the efforts to sustain it are the limited production of pepper, land conversion and pests. The aim of this study is (1) to identify the factors affecting the development of pepper farms based on the stakeholders’ perception in south Bangka Regency. The method used in this study is survey. To analyse the data, the study used qualitative analysis and AHP model. The result suggested that the factor that has the most influence on white pepper farm development is land.